The impact of rule updates on the performance of racewalkers and the classification of countries: An analysis at the Olympic Games - Mohamed Megahed; Zahraa Tarek (Universidad de Murcia, 2024)
Numerous controversies arose over the judgment of the racewalking events, and the rules were amended more than once. Before 1995, the rule required constant touch with the ground, and the need for a straight knee was only applied in the upright vertical posture. While, after 1995, the rule that applies today was published, which included two obvious changes. One related to maintaining a constantly straight knee through the first half of the stride, and the other to maintaining contact as seen by the human eye. This study aimed to investigate the impact of the last three modifications in racewalking rules on elite athletes' performance, athletes' eligibility, and nations' classification. Also, we investigated the regression between performance times of 20, and 50 km events and explanatory variables (BMI, and age). We collected data of 310 racewalkers from Olympic Games records (men) in 20km and 50km between 1956 and 2016. This period was divided into three stages according to the racewalking rules updates: Stage A (from 1996 to 2016), Stage B (from 1976 to 1992), and Stage C (from 1956 to 1972). There was a significant difference between all stages favoring stage A for Athlete's Performance. Stage A has the highest speeds (4.06±.23m/sec) for 20km with large ES (η2=.54, p=.000), and (3.71±.06m/sec) for 50km with large ES (η2=.769, p=.000) compared to others. The participants had the efficiency and the ability to finish the race with the least percentage of withdrawals under the current rule compared to other rules. Some countries emerged on the scene, i.e. China, Poland and Ecuador, and others disappeared under the current rule; while the regression model's results revealed a substantial link between time and explanatory parameters where (BConstant=58.219, P.000) for 20km and (BConstant=164.744, P.000) for 50km. Results proved that the elite walkers, the youngest and lowest in BMI, are the fastest and most efficient walkers under the current rule.